SPEARMAN CORRELATION ANALYSIS OF AIR AND BILLET TEMPERATURE IN ALUMINUM HOMOGENIZATION USING IoT-BASED REAL-TIME DATA COLLECTION - Afiqah, Filzah Amanina; Prasetyo, Murman Dwi; Sjafrizal, Teddy (Informatika, Universitas Jenderal Soedirman, 2024)
Understanding the correlation between the parameters involved in the homogenization process of aluminum billets contributes to better process control. As a critical step in the production of aluminum billets, failure to control the homogenization temperature can lead to variations in product quality and a negative effect on mechanical strength. To address this issue, this study aims to understand the correlation between air and billet temperature of homogenization using temperature data obtained from thermocouple sensors placed at different points in the oven and billet. The temperature data was collected in real time through an Internet of Things (IoT) network. Spearman correlation analysis was performed on the collected data to determine the relationship between temperatures at different measurement points. The analysis results show that the air temperature at the Z2 right point had a strong correlation with the billet temperature, with a correlation value of 0.90. In contrast, the correlation between air temperature and billet temperature at Z1 Left was lower, indicating a weaker correlation and resulting in uneven heat distribution. These results highlight the importance of controlling the air temperature at Z2 Right to improve the temperature distribution during heat treatment. In addition, this study provides a real case in the implementation of real-time monitoring technology for better understanding on industrial process, especially heat treatment process.